Prenatal Diagnosis of Vein of Galen Aneurysmal Malformation Allows Early Transumbilical Endovascular Treatment - Demartini, Zeferino, Jr; Koppe, Gelson Luis; Gatto, Luana A.M.; Sarquis, Ana Lucia; Francisco, Alexandre N.; Cardoso-Demartini, Adriane (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Neonates with vein of Galen aneurysmal malformation (VGAM) presenting with severe cardiac failure and pulmonary hypertension represent a challenge for endovascular therapy. When early treatment is required, the small femoral arteries in this population are usually difficult to cannulate. Alternatively, the umbilical vessels offer a natural pathway to reach the lesion. Therefore, prenatal diagnosis of VGAM allows for delivery planning, perinatal management, and embolization through umbilical approach, thus leading to better outcomes.
Keywords: vein of Galen malformations; arteriovenous malformations; prenatal diagnosis; umbilical arteries; newborn infant; endovascular procedures.